Talc synthesized low-temperature co-fired microwave dielectric ceramic and preparation method thereof
By using talc instead of some silicon and magnesium raw materials and adjusting the resonant frequency temperature coefficient, the performance instability problem of Li2MgSiO4 ceramic materials is solved, and the preparation of low-cost, high-performance low-temperature co-fired microwave dielectric ceramics is realized, which is suitable for microwave devices and LTCC multi-layer integrated modules.
Patent Information
- Application Number
- CN202510419738.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2025-07-18
AI Technical Summary
The existing Li2MgSiO4 ceramic materials have performance instability, especially due to limitations caused by SiO2 polymorphic transition and high sintering temperature, which affects its application in high frequency and highly integrated circuits.
Talc is used to replace some silicon and magnesium raw materials, and the resonant frequency temperature coefficient is adjusted by adding TiO2 or CaTiO3, and LAB glass is added to reduce the sintering temperature. Low-temperature co-fired microwave dielectric ceramics are prepared by solid-phase sintering method.
It realizes the low dielectric constant, low loss, and resonant frequency temperature coefficient of ceramic materials, which reduces production costs and meets the application requirements of LTCC multi-layer integrated modules.
Smart Images

Figure CN120329022A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electronic ceramics, and particularly relates to a talc-synthesized low-temperature co-fired microwave dielectric ceramic and a preparation method thereof. Background Art
[0002] As an indispensable part of radio frequency circuits, with the continuous development of circuits towards high frequency and high integration, the demand for low dielectric constant materials is increasing. Low dielectric constant materials can shorten the delay time of signal propagation; the Q value is a key performance index in practical applications such as radio frequency filter and oscillator design. A higher Q value has significant advantages in resonant circuit design, which is reflected in a lower energy loss rate and higher frequency selectivity; a near-zero temperature coefficient of resonant frequency can ensure the high stability of devices in an environment with temperature changes.
[0003] LTCC technology is a multi-layer integration technology that co-fires ceramic materials and metal conductors (such as Ag, Cu) below 900 °C, and is widely used in fields such as high-frequency communication, sensors, and electronic packaging to promote the development of device miniaturization and integration. Li2MgSiO4 ceramics have the advantages of high quality factor and low dielectric constant, but the required raw material SiO2 has the characteristic of polymorphic transformation, resulting in unstable material properties; moreover, Li2MgSiO4 ceramics have a relatively high sintering temperature and a large negative temperature coefficient of resonant frequency, which greatly limits their applications. The main component of talc is hydrated magnesium silicate (3MgO·4SiO2·H2O), which is one of the advantageous minerals in China. As one of the main domestic talc production areas, Guangxi has rich mineral reserves, high purity, and extremely low talc prices. Therefore, using talc to replace most of the silicon and magnesium raw materials required for synthesizing Li2MgSiO4 can avoid the instability of material properties caused by the polymorphic transformation of SiO2, while reducing costs and realizing the high-value application of talc. Summary of the Invention
[0004] The purpose of the present invention is to provide a talc-synthesized low-temperature co-fired microwave dielectric ceramic and a preparation method thereof, aiming to solve the problem of unstable properties of existing ceramic materials.
[0005] To achieve the above purpose, in the first aspect, the present invention provides a preparation method for a talc-synthesized low-temperature co-fired microwave dielectric ceramic, including the following steps:
[0006] Weigh talc, Li2CO3, and MgO powders, add absolute ethanol and perform the first wet grinding to obtain a first powder slurry;
[0007] Put the first powder slurry into a drying oven to dry and obtain dried powder;
[0008] Sieve the dried powder and put it into a muffle furnace for pre-sintering to obtain pre-sintered powder;
[0009] After adding M, LAB, and absolute ethanol to the cooled pre-sintered powder, perform the second wet grinding to obtain powder slurry two;
[0010] Dry the powder slurry two, granulate, and press it to obtain a green ceramic body;
[0011] Sinter the green ceramic body to obtain Li2MgSiO4 low-temperature co-fired microwave dielectric ceramic.
[0012] Among them, in "weigh talc, Li2CO3, and MgO powders, add absolute ethanol and perform the first wet grinding to obtain powder slurry one", according to the chemical formula Li 2-x MgSiO4 (x = 0 - 0.4) for batching, the mass ratio of the added absolute ethanol to Li 2- x MgSiO4 (x = 0 - 0.4) is 2:1, and the duration of the first wet grinding is 4 hours.
[0013] Among them, in "sieve the dried powder and then put it into a muffle furnace for pre-sintering, the pre-sintered powder", the sieving is carried out using an 80-mesh sieve, the pre-sintering temperature of the muffle furnace is 875 °C, and the calcination duration is 4 hours.
[0014] Among them, in "after adding M, LAB, and absolute ethanol to the cooled pre-sintered powder, perform the second wet grinding to obtain powder slurry two", according to Li 2-x MgSiO4 + ywt% M + zwt% LAB for batching, where x = 0 - 0.4, y = 30 - 50, z = 0 - 4, and M is TiO2 or CaTiO 3; The duration of the second wet grinding is 4 hours.
[0015] Among them, in "dry the powder slurry two, granulate, and press it to obtain a green ceramic body", the drying temperature is 60 - 100 °C; 8wt% PVA is used as a binder in the granulation.
[0016] Among them, in "sinter the green ceramic body to obtain Li2MgSiO4 low-temperature co-fired microwave dielectric ceramic", the sintering temperature is 850 - 1225 °C, and the duration is 4h.
[0017] In the second aspect, a talc-synthesized low-temperature co-fired microwave dielectric ceramic is prepared by using the talc-synthesized low-temperature co-fired microwave dielectric ceramic preparation method described in the first aspect. The dielectric constant ε of the talc-synthesized low-temperature co-fired microwave dielectric ceramic r = 5.42 - 15.20; the quality factor Q×f = 7467 - 70569 GHz, and the resonant frequency temperature coefficient τ f = -226.81 - 27.34 ppm / °C.
[0018] A preparation method of talc-synthesized low-temperature co-fired microwave dielectric ceramics of the present invention includes the following steps: weighing talc, Li2CO3 and MgO powders, adding absolute ethanol and performing the first wet grinding to obtain a first powder slurry; putting the first powder slurry into an oven for drying to obtain dried powder; sieving the dried powder and then putting it into a muffle furnace for pre-sintering to obtain pre-sintered powder; adding M, LAB and absolute ethanol to the cooled pre-sintered powder and then performing the second wet grinding to obtain a second powder slurry; drying the second powder slurry, granulating and pressing to obtain a ceramic green body; sintering the ceramic green body to obtain Li2MgSiO4 low-temperature co-fired microwave dielectric ceramics. The present invention uses Li + non-stoichiometric ratio to modify it; on the basis of modification, adjusting the resonance frequency temperature coefficient of the material by adding TiO2 or CaTiO3; on the basis of adjusting the resonance frequency temperature coefficient, adding LAB glass to reduce the sintering temperature of the material. The finally prepared ceramic formula has the characteristics of serialized dielectric constant, low loss, low sintering temperature and nearly zero resonance frequency temperature coefficient. By using talc to replace most of the silicon raw materials and magnesium raw materials required for synthesizing Li2MgSiO4, the instability of the SiO2 polymorphic transformation is avoided, the production cost of the ceramics is reduced, and at the same time, the resonance frequency temperature coefficient is nearly zero and the sintering temperature is reduced to 900 °C, making the ceramics have significant application potential and value in microwave devices and LTCC multi-layer integrated modules. Thus, the problem of unstable performance of existing ceramic materials is solved. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for use in the description of the embodiments or the prior art. Obviously, the following drawings are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can be obtained based on these drawings.
[0020] Figure 1 is a flow chart of a preparation method of talc-synthesized low-temperature co-fired microwave dielectric ceramics provided by the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0021] The following details the embodiments of the present invention. The examples of the embodiments are shown in the drawings, where the same or similar reference numerals represent the same or similar elements or elements with the same or similar functions from beginning to end. The embodiments described below with reference to the drawings are exemplary and are intended to explain the present invention and should not be construed as a limitation of the present invention.
[0022] Please refer to Figure 1 , in the first aspect, the present invention provides a preparation method of talc-synthesized low-temperature co-fired microwave dielectric ceramics, including the following steps:
[0023] S1 Weigh talc, Li2CO3 and MgO powders, add absolute ethanol and conduct the first wet grinding to obtain the first powder slurry.
[0024] According to the chemical formula Li 2-x MgSiO4 (x = 0 - 0.4) for batching, the mass ratio of the added absolute ethanol to Li 2-x MgSiO4 (x = 0 - 0.4) is 2:1, and the duration of the first wet grinding is 4 hours.
[0025] Specifically, weigh talc, Li2CO3 and MgO powders according to the chemical formula Li 2-x MgSiO4 (x = 0 - 0.4), add absolute ethanol and conduct the first wet grinding. The mass ratio of the added absolute ethanol to Li 2-x MgSiO4 (x = 0 - 0.4) is 2:1, and the duration of the wet grinding is 4 hours.
[0026] S2 Put the first powder slurry into an oven for drying to obtain the dried powder.
[0027] The drying temperature is 60 - 100 °C.
[0028] Specifically, put the powder after wet grinding in step S1 into an oven for drying, and the drying temperature range is 60 - 100 °C.
[0029] S3 Sieve the dried powder and then put it into a muffle furnace for pre - calcination to obtain the pre - calcined powder.
[0030] The sieving uses a 80 - mesh sieve, the pre - calcination temperature of the muffle furnace is 875 °C, and the calcination duration is 4 hours.
[0031] Specifically, sieve the powder dried in step S2 using an 80 - mesh sieve, and then put it into a muffle furnace for pre - calcination. The pre - calcination temperature is 875 °C, and the calcination duration is 4 hours.
[0032] S4 Add M, LAB and absolute ethanol to the cooled pre - calcined powder and then conduct the second wet grinding to obtain the second powder slurry.
[0033] According to Li 2-x MgSiO4 + ywt% M + zwt% LAB for batching, where x = 0 - 0.4, y = 30 - 50, z = 0 - 4, M is TiO2 or CaTiO 3; The duration of the second wet grinding is 4 hours.
[0034] Specifically, after cooling the calcined powder to room temperature, according to Li 2-xMgSiO4 + y wt% M + z wt% LAB. Weigh the powder, M, and LAB after pre-burning in step 3, where x = 0 - 0.4, y = 30 - 50, z = 0 - 4, and M is TiO2 or CaTiO3. Add absolute ethanol for the second wet grinding, and the duration of the second wet grinding is 4 hours.
[0035] S5 Dry the powder slurry two, granulate and press it to obtain a green ceramic body;
[0036] The drying temperature is 60 - 100 °C; 8 wt% PVA is used as a binder in the granulation.
[0037] Specifically, dry the powder after wet grinding in step S4 within the range of 60 - 100 °C, use 8 wt% PVA as a binder for granulation, and press it into a green ceramic body;
[0038] S6 Sinter the green ceramic body to obtain a Li2MgSiO4 low-temperature co-fired microwave dielectric ceramic.
[0039] The sintering temperature is 850 - 1225 °C, and the duration is 4 h.
[0040] Specifically, sinter the green ceramic body obtained in step S5 within the range of 850 - 1225 °C, and the sintering duration is 4 hours to complete the preparation.
[0041] Example 1:
[0042] Using talc powder as the raw material, a low-cost and high-temperature stability Li2MgSiO4 low-temperature co-fired microwave dielectric ceramic is prepared by the solid-phase sintering method. The specific implementation steps are as follows:
[0043] (1) Weigh a certain amount of talc, Li2CO3, and MgO powders according to the chemical formula Li 1.8 MgSiO4, add absolute ethanol, and the mass ratio of Li 1.8 MgSiO4 to absolute ethanol is 1:2, carry out ball milling, the ball milling duration is 4 hours, and the rotation speed is 500 revolutions per minute;
[0044] (2) Put the powder slurry obtained in step (S1) into a drying oven and dry it at 85 °C;
[0045] (3) Put the sieved powder in step (S2) into a muffle furnace and pre-burn it at 875 °C for 4 hours of heat preservation;
[0046] (4) Add absolute ethanol to the powder after calcination in step (S3), the mass ratio of the powder to absolute ethanol is 1:2, carry out the second wet grinding, the duration of the second wet grinding is 4 hours, and the rotation speed is 500 revolutions per minute;
[0047] (5) placing the powder slurry obtained in step (S4) into a drying oven, drying at 85° C., granulating the slurry using 8 wt % PVA as a binder, passing the slurry through an 80-mesh sieve, and pressing the slurry into a ceramic green body using a tablet press;
[0048] (6) sintering the green body of step (S5) at 1050° C., 1075° C., 1100° C., and 1125° C., respectively, with a holding time of 4 hours;
[0049] (7) The microwave dielectric properties of the samples were tested by network analyzer at 1050-1125°C.
[0050] ε r =5.95-6.08, Q×f=39261-55723GHz, τ f =-192.49--186.04ppm / ℃.
[0051] In this case, when the sintering temperature is 1075℃, the material exhibits excellent comprehensive dielectric properties ε r =6.08, Q×f=55723GHz, τ f =-189.28ppm / ℃.
[0052] Embodiment 2:
[0053] The implementation steps are as follows:
[0054] Using talc powder as raw material, low-cost, high-temperature-stability Li2MgS1O4 low-temperature co-fired microwave dielectric ceramics were prepared by solid-phase sintering. The specific implementation steps are as follows:
[0055] (1)-(3) are the same as in Example 1;
[0056] (4) The powder calcined in step (S3) is treated according to the chemical formula Li 1.8 MgS iO4+50wt%TiO2 are prepared, and the rest is the same as in Example 1;
[0057] (5) Same as Example 1;
[0058] (6) sintering the green body of step (S5) at 975° C., 1000° C., 1025° C., and 1050° C., respectively, with a holding time of 4 hours;
[0059] (7) The microwave dielectric properties of the samples were tested by network analyzer in the range of 975-1050°C.
[0060] ε r =9.85-10.98, Q×f=20681-70569GHz, τ f= -4.39 - 2.38 ppm / °C.
[0061] In this example, when the sintering temperature is 1025 °C, the material exhibits excellent comprehensive dielectric properties.
[0062] ε r = 10.98, Q×f = 70569 GHz, τ f = -4.39 ppm / °C, the temperature coefficient of resonant frequency is nearly zero, and the dielectric properties are excellent.
[0063] Example 3:
[0064] The implementation steps are as follows:
[0065] Using talc powder as the raw material, a low-cost, high-temperature stability Li2MgSiO4 low-temperature co-fired microwave dielectric ceramic is prepared by the solid-phase sintering method. The specific implementation steps are as follows:
[0066] (1)-(3) are the same as in Example 1.
[0067] (4) The powder calcined in step (S3) is proportioned according to the chemical formula Li 1.8 MgSiO4 + 40 wt% CaTiO3, and the others are the same as in Example 1;
[0068] (5) is the same as in Example 1;
[0069] (6) The green body in step (S5) is sintered at 1025 °C, 1050 °C, 1075 °C, and 1100 °C respectively, and the holding time is 4 hours;
[0070] (7) The microwave dielectric properties of the prepared samples in the range of 1025 - 1100 °C are tested by a network analyzer.
[0071] ε r = 11.47 - 14.97, Q×f = 11323 - 20614 GHz, τ f = -6.42 - 4.29 ppm / °C.
[0072] In this example, when the sintering temperature is 1100 °C, the material exhibits excellent comprehensive dielectric properties.
[0073] ε r = 13.65, Q×f = 20614 GHz, τ f = 4.29 ppm / °C.
[0074] Example 4:
[0075] The implementation steps are as follows:
[0076] Using talc powder as the raw material, a low-cost and high-temperature stability Li2MgSiO4 low-temperature co-fired microwave dielectric ceramic is prepared by the solid-phase sintering method. The specific implementation steps are as follows:
[0077] (1)-(3) are the same as in Example 1.
[0078] (4) The powder calcined in step (S3) is formulated according to the chemical formula Li 1.8 MgSiO4 + 50 wt% TiO2 + 3 wt% LAB, and the others are the same as in Example 1;
[0079] (5) is the same as in Example 1;
[0080] (6) The green body in step (S5) is sintered at 850 °C, 875 °C, 900 °C, and 925 °C respectively, and the holding time is 4 hours;
[0081] (7) The microwave dielectric properties of the prepared samples in the range of 850 - 925 °C are tested by a network analyzer, ε r = 9.91 - 10.60, Q×f = 33763 - 38738 GHz, τ f = -0.54 - 1.87 ppm / °C.
[0082] In this example, when the sintering temperature is 900 °C, it has the optimal dielectric properties, ε r = 10.54, Q×f = 38738 GHz, τ f = -0.54 ppm / °C, with excellent dielectric properties, a near-zero temperature coefficient of resonant frequency, and meeting the LTCC temperature requirements.
[0083] In the second aspect, a talc-synthesized low-temperature co-fired microwave dielectric ceramic is prepared by using the talc-synthesized low-temperature co-fired microwave dielectric ceramic preparation method described in the first aspect. The dielectric constant ε r of the low-temperature co-fired microwave dielectric ceramic is 5.42 - 15.20; the quality factor Q×f = 7467 - 70569 GHz, and the temperature coefficient of resonant frequency τ f = -226.81 - 27.34 ppm / °C.
[0084] Table 1 shows the dielectric properties of the low-cost and high-temperature stability Li2MgSiO4 low-temperature co-fired microwave dielectric ceramic obtained in the present invention.
[0085]
[0086] Table 1
[0087] The above-disclosed is only a preferred embodiment of a talc-synthesized low-temperature co-fired microwave dielectric ceramic and its preparation method of the present invention. Of course, the scope of rights of the present invention cannot be limited thereby. Those of ordinary skill in the art can understand all or part of the processes of implementing the above embodiments, and the equivalent changes made according to the claims of the present invention still fall within the scope covered by the invention.
Claims
1. A preparation method of a talc-synthesized low-temperature co-fired microwave dielectric ceramic, characterized in that, It includes the following steps: Weigh talc, Li2CO3 and MgO powders, add anhydrous ethanol and conduct the first wet grinding to obtain the first powder slurry; Put the first powder slurry into a drying oven for drying to obtain dried powder; Sieve the dried powder and then put it into a muffle furnace for pre-sintering to obtain pre-sintered powder; Add M, LAB and anhydrous ethanol to the cooled pre-sintered powder and then conduct the second wet grinding to obtain the second powder slurry; Dry the second powder slurry, granulate and press it to obtain a ceramic green body; Sinter the ceramic green body to obtain Li2MgSiO4 low-temperature co-fired microwave dielectric ceramic.
2. The preparation method of the talc-synthesized low-temperature co-fired microwave dielectric ceramic according to claim 1, characterized in that, In "weighing talc, Li2CO3 and MgO powders, adding absolute ethanol and performing the first wet grinding to obtain the first powder slurry", according to the chemical formula Li 2-x MgSiO4 (x = 0 - 0.4) for batching, the mass ratio of the added absolute ethanol to Li 2-x MgSiO4 (x = 0 - 0.4) is 2:1, and the duration of the first wet grinding is 4 hours.
3. The preparation method of the talc-synthesized low-temperature co-fired microwave dielectric ceramic according to claim 1, characterized in that, In "Sieve the dried powder and then put it into a muffle furnace for pre-sintering to obtain pre-sintered powder", the sieving is carried out using a 80-mesh sieve, the pre-sintering temperature of the muffle furnace is 875 °C, and the calcination duration is 4 hours.
4. The preparation method of the talc-synthesized low-temperature co-fired microwave dielectric ceramic according to claim 1, characterized in that In "adding M, LAB and absolute ethanol to the cooled pre-fired powder and then performing the second wet grinding to obtain the powder slurry two", according to Li 2-x MgSiO4 + y wt% M + z wt% LAB for batching, where x = 0 - 0.4, y = 30 - 50, z = 0 - 4, and M is TiO2 or CaTiO 3; The duration of the second wet grinding is 4 hours.
5. The preparation method of the talc-synthesized low-temperature co-fired microwave dielectric ceramic according to claim 1, characterized in that, In "Dry the second powder slurry, granulate and press it to obtain a ceramic green body", the drying temperature is 60 - 100 °C; 8wt% PVA is used as a binder in the granulation.
6. The preparation method of the talc-synthesized low-temperature co-fired microwave dielectric ceramic according to claim 1, characterized in that, In "Sinter the ceramic green body to obtain Li2MgSiO4 low-temperature co-fired microwave dielectric ceramic", the sintering temperature is 850 - 1225 °C, and the duration is 4 h.
7. A talc-synthesized low-temperature co-fired microwave dielectric ceramic, characterized in that, Prepared by the method for preparing talc-synthesized low-temperature co-fired microwave dielectric ceramics according to any one of claims 1-6, the dielectric constant ε of the talc-synthesized low-temperature co-fired microwave dielectric ceramics r = 5.42 - 15.20; The quality factor Q×f = 7467 - 70569 GHz; Temperature coefficient of resonant frequency τ f = -226.81 - 27.34 ppm / °C.